A Study on Role of Organic Foods on Consumer and Their Level of Trust - M , Snekha.; B, Sreeya (International Journal of Membrane Science and Technology, 2023)
Organic foods have a greater impact in human health and environment sustainability. This study aims to understand the consumption pattern of organic food products and their trust level. The study was conducted using a well-structured questionnaire administered to 139 consumers of organic food products. Researcher used SPSS to analyse the data. It was found that friends and relatives serve as main source of information about organic food products and the main reason for consuming organic food products is to stay healthy. The main concern about the organic food products is about the lack of certification level.